2016
DOI: 10.1158/0008-5472.can-16-0579
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Stiffness and Hypoxia Modulate the Integrin-Linked Kinase ILK to Control Breast Cancer Stem-like Cells

Abstract: Breast tumors are stiffer and hypoxic compared to nonmalignant breast tissue. Here we report that stiff and hypoxic microenvironments promote the development of breast cancer stem-like cells (CSC) through modulation of the integrin-linked kinase ILK. Depleting ILK blocked stiffness and hypoxia-dependent acquisition of CSC marker expression and behavior, whereas ectopic expression of ILK stimulated CSC development under softer or normoxic conditions. Stiff microenvironments also promoted tumor formation and met… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
117
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(124 citation statements)
references
References 52 publications
4
117
1
1
Order By: Relevance
“…Variance in these physical conditions may determine whether the environment is conducive for cell movement. For example, the ECM may facilitate cell motility by providing a stiff substrate for cellular focal adhesion necessary for cell movement (38). Conversely, the ECM structure and organization can inhibit movement depending on characteristics such as fiber composition and alignment (39).…”
Section: Movement Ability Is Essential For Mobile Foraging Of Pre-metmentioning
confidence: 99%
“…Variance in these physical conditions may determine whether the environment is conducive for cell movement. For example, the ECM may facilitate cell motility by providing a stiff substrate for cellular focal adhesion necessary for cell movement (38). Conversely, the ECM structure and organization can inhibit movement depending on characteristics such as fiber composition and alignment (39).…”
Section: Movement Ability Is Essential For Mobile Foraging Of Pre-metmentioning
confidence: 99%
“…Presence of hypoxia is correlated with poor prognosis and treatment resistance in breast cancer patients [100]. Recently, it was shown that hypoxic and stiff breast tumors promote proliferation of breast cancer stem-like cells [101], which, in turn, can mediate resistance to therapy [102]. …”
Section: Ecm Mediates Treatment Resistancementioning
confidence: 99%
“…Biophysical cues in the tumor microenvironment are considered to be key and novel regulators of CSC maintenance and tumorigenic potential. In breast cancer cells and hepatocellular carcinoma cells, increasing the matrix stiffness of tumor cells can upregulate the expression of CSC biomarkers and self‐renewal ability. We cultured the CRC cell line HCT‐116 in a stiffness gradient of culture matrix and found that the mRNA and protein levels of the CSC biomarkers increased with the increased stiffness of culture matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that extracellular matrix (ECM) stiffness is part of the physical microenvironment of tumor cells. The extracellular physical signals are transformed into intracellular biological signals through the “extracellular matrix‐cell membrane receptor‐intracellular molecule” pathway, also called the “mechanical‐biological” signal transduction pathway, and this transformation plays an important role in screening and maintaining the CSC phenotype . It has been proven that the integrin family acts as a switch, and Yes‐associated protein (YAP) is a key molecule in this pathway …”
Section: Introductionmentioning
confidence: 99%